The finite element method for solid and structural mechanics / O.C. Zienkiewz, R.L. Taylor - Zienkiewcz, O.C
This book is the key text and reference for engineers, researchers and senior students dealing with the analysis and modeling of structures, from large civil engineering projects such as dams to aircraft structures and small engineered components.